P3.94 Does mass drug administration with azithromycin for trachoma control have an impact on the prevalence and macrolide resistance of genital mycoplasma genitalium infection?. (8th July 2017) - Harrison, M; Marks, M; Harding-Esch, E; Pond, MJ; Butcher, R; Solomon, A; Tan, NK; Nori, A; Kako, H; Mabey, D; Sadiq, ST
Abstract : Introduction: The first round of Mass Drug Administration (MDA) with 1g oral azithromycin for ocular Chlamydia trachomatis (CT) infection, which is a key component of trachoma control strategies, concomitantly reduced genital CT infection in the Solomon Islands. However, this dose is known to be sub-optimal for the treatment of genital Mycoplasma genitalium (MG) infection and may also encourage emergence of antimicrobial resistance (AMR) to macrolides in MG. Methods: Pre-MDA and 6 months post-MDA CT-negative self-collected vulvo-vaginal swabs from women attending three outpatient antenatal clinics (Honiara, Solomon Islands), already investigated for the impact of MDA on genital CT prevalence, were tested for MG infection using nucleic acid amplification. MG positive samples were subsequently tested for macrolide resistance by sequencing domain V of 23S rRNA DNA region of MG. Results: MG positivity was found in 11.9% (28/236) of women pre-MDA and in 10.9% (28/256) 6 months post-MDA (p=0.7467). 22 MG positives from each of the pre-MDA and post-MDA samples were sequenced, all showing a macrolide susceptible genotype. Conclusion: A single MDA round in an island population with apparent high MG prevalence with 1g azithromycin did not impact on either MG positivity or detection of genetically determined macrolide resistance in this population, in contrast to decreased genital CT positivity in the same population. It is unclear if this apparent lack of impact is due to inadequate efficacy of single-dose azithromycin or transmission dynamics of the infection. Further investigation of the impact of multiple rounds of MDA on antibiotic-experienced and -naïve populations is warranted.